العولمة والتنميط الثقافي في السرديات المرئية -دراسة تحليلية لمضامين الدراما المرئية الغربية- - صالح محمد صبري (lark, 2019)
This research deals with the phenomenon of cultural globalization, its concept, dimensions and conventions, which is mainly implemented through media. The American visual drama, particularly, received by viewers via visual means of communication (television, cinema, telephone and computer) as movies, serials or advertisements, is the most effective tool for translating, publishing, promoting and normalizing the globalization culture. Thus, peoples are stereotyped with uniform values​and a common lifestyle governed by the same laws, which contradict with the peoples’ culture sometimes. Visual drama plays a major role in infusing and glorifying the new values in a thrilling and appealing manner and at the same time, it fights other cultural values that intersect with the objective of globalization in general.